Short CO2 Exposure for Inhibition of Postharvest Grey Mould of Pomegranate Fruit - Montesinos-Herrero, Clara; Taberner, Verònica; Guardado, Aurora; Del-Río, Miguel A.; Palou, Lluís (2017)
Pomegranate (Punica granatum L.) is an expanding crop due to the high antioxidant activity and benefits for human health provided by this fruit. As new markets based on the manufacture of derived functional food products are arising, longer storage life of fresh pomegranates is required. An important factor limiting storability is postharvest decay due to grey mould, caused by Botrytis cinerea. In Spain and other important producing areas no postharvest chemical treatments of pomegranate are allowed and alternative antifungal treatments are required. Exposure to CO2-enriched atmospheres is known to provide fungistatic effects against major postharvest pathogens. In this work, pomegranates ‘Mollar de Elche’ were artificially inoculated with B. cinerea and exposed 24 h later to 0 (ambient atmosphere, control), 15, 50 or 95 kPa CO2 at 20°C and 90% RH for 48 h. Exposure of fruit to 0 and 95 kPa CO2 was also tested at 20°C for 24 h or 35°C for 48 h. Incidence and severity of grey mould were evaluated after 2, 5, 10 and 12 days of incubation at 20°C and 90% RH. After 5 days of incubation, the incidence of grey mould on fruit treated with 95 and 50 kPa CO2 at 20°C for 48 h was 92 and 82% lower than on control fruit, respectively. These reductions were 60 and 47% after 10 days. At the end of the incubation period, the severity of grey mould on fruit exposed to 95 and 50 kPa CO2 was reduced by 43 and 30% with respect to control fruit, respectively. Grey mould inhibition by treatment with 95 kPa CO2 for 48 h was lower at 35 than at 20°C. Exposure of pomegranates to 15 kPa CO2 for 48 h or 95 kPa CO2 for 24 h at 20°C did not affect the development of grey mould.